2016
DOI: 10.1080/10749357.2015.1116227
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity in chronic home-living and sub-acute hospitalized stroke patients using objective and self-reported measures

Abstract: In HOM significantly more steps were performed and higher EE values were measured. However, participation in moderate activities and time spent on therapy were less in HOM. Evaluating PA with quantitative measures is feasible in both chronic home-living and sub-acute hospitalized patients with stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 30 publications
1
29
1
3
Order By: Relevance
“…A majority of participants were rather physically inactive, as shown by their PASE-scores [33] (see Table 1). This is confirmed by existing literature, which showed that PA participation among persons with stroke is normally lower compared with a general population [36, 37], and that persons with stroke spend more time sitting and less time in activity than age-matched peers [9]. Most of the participants did not distinguish between general physical activity and planned exercise, these terms were used interchangeably.…”
Section: Discussionsupporting
confidence: 78%
“…A majority of participants were rather physically inactive, as shown by their PASE-scores [33] (see Table 1). This is confirmed by existing literature, which showed that PA participation among persons with stroke is normally lower compared with a general population [36, 37], and that persons with stroke spend more time sitting and less time in activity than age-matched peers [9]. Most of the participants did not distinguish between general physical activity and planned exercise, these terms were used interchangeably.…”
Section: Discussionsupporting
confidence: 78%
“…The strengths of this study are its large sample size, its broad inclusion criteria, the use of accelerometers to assess PA and the large number of PA hours recorded. Regarding sample size, this study is the largest when compared to other studies in Europe (12,13,(16)(17)(18)41), the USA (20,21,32) and Australia (14,19). Regarding inclusion criteria, and contrary to previous studies (12,32,47,48), we included patients with cognitive impairment/confusion as they are at increased risk of post-hospitalization functional decline (28,39).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Further, the data collected can be analyzed with algorithms that classify locomotion and nonlocomotion periods in everyday life (15). Still, there is a paucity of studies assessing PA levels by accelerometry in hospitalized older patients (12)(13)(14)(16)(17)(18)(19)(20)(21)(22). In a previous paper, Lim et al reported that the PA levels of 38 hospitalized older patients were very low and that most PA was sustained over short periods (12).…”
Section: Introductionmentioning
confidence: 99%
“…The strengths of this study are its large sample size, its broad inclusion criteria, the use of accelerometers to assess PA and the large number of PA hours recorded. Regarding sample size, this study is the largest when compared to other studies in Europe (12,13,(16)(17)(18)41), the USA (20,21,32) and Australia (14,19).…”
Section: Strengths and Limitationsmentioning
confidence: 94%